The Tallons - March, William, 1893-1954 (Book collections on Project MUSE., 2014)
In The Tallons, the second book in his " Pearl County" series, William March continues to hone his distinctive style but for the first time creates a work that follows a continuous, linear narrative. Here, March' s masterful development of the theme of jealousy highlights his growing maturity and ambition as a writer. Set in a rural Alabama backwater, The Tallons tells the story of two farm boys, Andrew and Jim Tallon. Their placid and predictable life is upended by a girl from Georgia, Myrtle Bickerstaff. The conflict which engulfs these three is built up from a series of carefully chosen and.